Pengaruh Efektivitas Komunikasi Melalui Learning Management System Celoe Terhadap Minat Belajar Mahasiswa Telkom University - Dewi Annisa; Asaas Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The Covid-19 pandemic has impacts on various sectors, one of which is education. The impact on education is the change of face-to-face learning system to be online learning. Instructional media has an important role as supporting facilities so that online learning can be implemented properly and smoothly. Telkom University creates Learning Management System CeLOE as online learning media. Through LMS CeLOE, the communication process between students and lecturers occur. However, the LMS CeLOE server is often down causing various parties cannot access LMS CeLOE, especially students of Telkom University. This causes the communication process to be ineffective so that it can impact the student learning interest. Therefore, this study aims to find out and analyze the effect of communication effectiveness through Learning Management System CeLOE on the student learning interest of Telkom University. This study used a quantitative method with a quantitative descriptive type. The sampling used a non-probability sampling technique with100 respondents. The respondents were active students of Telkom University. Based on the results of the hypothesis test, it shows that in this study, there is a significant effect between communication effectiveness on learning interset. This effect can be seen from the results of the determination coefficient of 63%, and another 27% is influenced by other factors notanalyzed in this study. Keywords: Communication, Communication Effectiveness, Learning Interest, Learning Management System (LMS), Online Learning